Predatory behavior of gambusia punctata (Poey, 1854) on Aedes aegypti (Linnaeus, 1762) larvae based on visual detection in a controlled experimental system - Argota Pérez, George (2024)
The objective was to evaluate the predatory behavior of Gambusia punctata (Poey, 1854) on Aedes aegypti (Linnaeus, 1762) larvae given its visual detection in a controlled experimental system. Two males and eight females of G. punctata were placed in a plastic container with submerged aquatic plants in the first third of the container. For the first three days, 30 A. aegypti larvae were supplied daily. A device was designed to distribute the mosquito larvae uniformly across the container's surface. A vertical plastic sheet was introduced in the second third of the container, restricting the fish to the first third. Four millimeter mesh cylinders were placed near the vegetation, designed to confine two larvae within each cylinder. Predatory response was assessed based on detection time and near-total permanence of the fish close to the cylinders. The experiment was replicated twice. Detection times were similar between replicates (6.01±0.21 s and 6.04±0.18 s), but replicate 1 showed greater variability and lower precision compared to replicate 2, which demonstrated higher consistency. No statistically significant differences were found. It was concluded that G. punctata effectively detects A. aegypti larvae when visible, but detection decreases when larvae are hidden, suggesting the use of other senses. The variability in detection times highlights the influence of experimental factors.